Anosognosia is associated with increased prevalence and faster development of neuropsychiatric symptoms in mild cognitive impairment - Wang, Sharon; Mimmack, Kayden; Cacciamani, Federica; Elnemais Fawzy, Michael; Munro, Catherine; Gatchel, Jennifer; Marshall, Gad A.; Gagliardi, Geoffroy; Vannini, Patrizia (Frontiers in Aging Neuroscience, 2024)
Introduction Both the loss of awareness for cognitive decline (a. k.a anosognosia) and neuropsychiatric symptoms (NPS) are common in patients with Alzheimer's disease (AD) dementia, even in prodromal stages, and may exacerbate functional impairment and negatively impact caregiver burden. Despite the high impact of these symptoms on patients and their caregivers, our knowledge of how they develop across the AD spectrum is limited. Here, we explored the cross-sectional and longitudinal associations between anosognosia and NPS in individuals with mild cognitive impairment (MCI). Methods We included 237 participants from the Alzheimer's Disease Neuroimaging Initiative (ADNI) with a baseline clinical diagnosis of MCI. Everyday Cognition (ECog) questionnaire scores were used to measure complaints from participants and study-partners at baseline and annually over a mean of 4.29 years [standard deviation (SD) = 2.72]. Anosognosia was defined as the study-partner having an ECog score ≥2.5/4 and the participant having an ECog score < 2.5/4 on their baseline measure and their last observation without more than two consecutive deviating observations during the follow-up period. The 12-item study-partner-rated Neuropsychiatric Inventory determined the presence or absence of specific NPS. Survival analyses were performed to analyze the frequency and temporal onset of NPS over time in individuals with and without anosognosia. Results Thirty-eight out of 237 participants displayed anosognosia. Groups had similar lengths of follow-up at baseline (p > 0.9), though participants with anosognosia had lower MMSE scores (p = 0.049) and a higher proportion of amyloid-positivity using PET (p < 0.001. At baseline, the frequencies of agitation (p = 0.029) and disinhibition (p < 0.001) were higher in the anosognosia group compared to the non-anosognosia group. Survival analyses showed earlier onset of seven of the 12 NPS in the anosognosia group (p's < 0.001). Discussion Loss of awareness for cognitive decline is associated with greater frequency and earlier onset of NPS over time in participants with MCI. These results support the hypothesis of a potential common underlying neurophysiological process for anosognosia and NPS, a finding that needs to be addressed in future studies.